Peningkatan Omset Penjualan dengan Teknologi Pemasaran Online serta Pelatihan Microlearning Pelaporan Keuangan dan Perpajakan pada Fashion Chabudin Store - Pertiwi, Suci; Yolanda, Yola; Tarihoran, Anita; Tarigan, Purnaya Sari (Jurnal Pengabdian Pada Masyarakat METHABDI, 2025)
Fashion Chabudin Store as one of the UMKM in Karo Regency, North Sumatra, has great potential to become a unit in increasing sales turnover with online marketing technology and knowledge in microlearning in making financial and tax reports. The purpose and benefits of this activity are so that Fashion Chabudin Store employees know and understand how to increase sales turnover with online marketing technology and improve microlearning training in financial and tax reporting. The community service team conducted a survey that they had never and did not know how to market goods online and had never received training in making correct financial and tax reports, in accordance with applicable standards and regulations. The implementation of the community service will be carried out in May 2025. The activity was carried out by presenting material, direct practice in increasing Sales Turnover with Online Marketing Technology and continued with microlearning training in financial and tax reporting by the community service team. The results of the community service at the Fashion Chabudin Store, the owner and employees of the Fashion Chabudin Store have understood how to increase sales turnover, by using online marketing technology and understand how to make financial and tax reports